The CCR2/CCL2 Interaction Mediates the Transendothelial Recruitment of Intravascularly Delivered Neural Stem Cells to the Ischemic Brain - Andres, Robert H. (2011)
BACKGROUND AND PURPOSE: The inflammatory response is a critical component of ischemic stroke. In addition to its physiological role, the mechanisms behind transendothelial recruitment of immune cells also offer a unique therapeutic opportunity for translational stem cell therapies. Recent reports have demonstrated homing of neural stem cells (NSC) into the injured brain areas after intravascular delivery. However, the mechanisms underlying the process of transendothelial recruitment remain largely unknown. Here we describe the critical role of the chemokine CCL2 and its receptor CCR2 in targeted homing of NSC after ischemia. METHODS: Twenty-four hours after induction of stroke using the hypoxia-ischemia model in mice CCR2(+/+) and CCR2(−/−) reporter NSC were intra-arterially delivered. Histology and bioluminescence imaging were used to investigate NSC homing to the ischemic brain. Functional outcome was assessed with the horizontal ladder test. RESULTS: Using NSC isolated from CCR2(+/+) and CCR2(−/−) mice, we show that receptor deficiency significantly impaired transendothelial diapedesis specifically in response to CCL2. Accordingly, wild-type NSC injected into CCL2(−/−) mice exhibited significantly decreased homing. Bioluminescence imaging showed robust recruitment of CCR2(+/+) cells within 6 hours after transplantation in contrast to CCR2(−/−) cells. Mice receiving CCR2(+/+) grafts after ischemic injury showed a significantly improved recovery of neurological deficits as compared to animals with transplantation of CCR2(−/−) NSC. CONCLUSIONS: The CCL2/CCR2 interaction is critical for transendothelial recruitment of intravascularly delivered NSC in response to ischemic injury. This finding could have significant implications in advancing minimally invasive intravascular therapeutics for regenerative medicine or cell-based drug delivery systems for central nervous system diseases.